2016
DOI: 10.26417/ejser.v6i1.p27-41
|View full text |Cite
|
Sign up to set email alerts
|

Communication about Sex-Reproductive Health Issues with Adolescents: A Taboo among Malaysian Parents?

Abstract: Despite of the various attempts to implement safety practices in school, there still many unresolved issues related to students' safety in schools. This study aimed to explore and examine current safety management practices in Malaysian primary schools and the type of safety management plans adopted by the administrators for ensuring students' safety. The sample of this study consisted of 141 School Headmasters and Deputy Headmasters (Administration and Curriculum, Student Affairs or Co-curriculum), randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
1
6
1
1
Order By: Relevance
“…As sexual abstinence may be one strategy to prevent STI contraction, we first examined whether negative body image was associated with one’s experience of partnered sex. Although the topic of sexual and reproductive health is not openly discussed in Malaysia (Ismail & Abd Hamid, 2016 ), the prevalence rate of sexual experience in our sample (51%) was similar to what has been found in undergraduate students in the United States (~ 50%; Gillen & Markey, 2014 ; Schooler et al, 2005 ). The prevalence rate in the current study was higher than what was found in Durex’s Sexual Health and Intimate Wellness Survey that was conducted with 1089 Malaysians aged 18–30 years from April to May 2022 (Hassandarvish, 2022 ; 35%) and an earlier survey with 1327 students from public universities in Selangor, who were predominantly Muslim (98%) and single (71%; Sham et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
“…As sexual abstinence may be one strategy to prevent STI contraction, we first examined whether negative body image was associated with one’s experience of partnered sex. Although the topic of sexual and reproductive health is not openly discussed in Malaysia (Ismail & Abd Hamid, 2016 ), the prevalence rate of sexual experience in our sample (51%) was similar to what has been found in undergraduate students in the United States (~ 50%; Gillen & Markey, 2014 ; Schooler et al, 2005 ). The prevalence rate in the current study was higher than what was found in Durex’s Sexual Health and Intimate Wellness Survey that was conducted with 1089 Malaysians aged 18–30 years from April to May 2022 (Hassandarvish, 2022 ; 35%) and an earlier survey with 1327 students from public universities in Selangor, who were predominantly Muslim (98%) and single (71%; Sham et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
“…Although a closer assessment reveals that the image does contribute to the verbal information in P4 via an Extension type of text-image relation, more needs to be known as to why the image is used by MOH instead of, for instance, a scientific drawing of the female reproductive organ. Since we have no access to MOH's insights on this, we are of the opinion that the yellow orchid image may have been used to represent women in a culturally appropriate manner, given the context where sex reproductive health issues still remain a taboo among many Malaysians (Ismail & Hamid, 2016). Second, concerning the use of Malay language in the posters: since the posters are in it makes perfect sense that the analysis could also have been done from the Malay perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from that, there is a limitation when discussing this issue between parents and adolescents as it is deemed as taboo and contradicts with the customs and beliefs (Abd Hamid & Ismail, 2016). This poses a researcher a question: if discussing about sex is forbidden, how do we promote the knowledge of SRH that brings benefit for adolescents?…”
Section: Limitations Of Srh Studiesmentioning
confidence: 99%